Are Cu2Te‐Based Compounds Excellent Thermoelectric Materials?. Issue 49 (16th October 2019) - Zhao, Kunpeng; Liu, Ke; Yue, Zhongmou; Wang, Yancheng; Song, Qingfeng; Li, Jian; Guan, Mengjia; Xu, Qing; Qiu, Pengfei; Zhu, Hong; Chen, Lidong; Shi, Xun
Abstract: Most of the state‐of‐the‐art thermoelectric (TE) materials exhibit high crystal symmetry, multiple valleys near the Fermi level, heavy constituent elements with small electronegativity differences, or complex crystal structure. Typically, such general features have been well observed in those well‐known TE materials such as Bi2 X3 ‐, SnX‐, and PbX‐based compounds (X = S, Se, and Te). The performance is usually high in the materials with heavy constituent elements such as Te and Se, but it is low for light constituent elements such as S. However, there is a great abnormality in Cu2 X‐based compounds in which Cu2 Te has much lower TE figure of merit ( zT ) than Cu2 S and Cu2 Se. It is demonstrated that the Cu2 Te‐based compounds are also excellent TE materials if Cu deficiency is sufficiently suppressed. By introducing Ag2 Te into Cu2 Te, the carrier concentration is substantially reduced to significantly improve the zT with a record‐high value of 1.8, 323% improvement over Cu2 Te and outperforms any other Cu2 Te‐based materials. The single parabolic band model is used to further prove that all Cu2 X‐based compounds are excellent TE materials. Such finding makes Cu2 X‐based compounds the only type of material composed of three sequent main group elements that all possess very high zT   s above 1.5. Abstract : By introducing Ag2 Te into Cu2 Te, the phase‐transition features are well tuned and the high carrier concentration is substantially reduced, leading to a record‐high zT of 1.8. It is demonstrated that Cu2 Te, Cu2 S, and Cu2 Se are all excellent thermoelectric (TE) materials that are beyond all other state‐of‐the‐art TE materials.